Mutation Detection in MYO15A Gene in an Iranian Family with Non-Syndromic Hearing Loss - Mostafa Neissi; Misagh Mohammadi-Asl; Mojdeh Roghani; Adnan Issa Al-Badran; Javad Mohammadi-Asl (International Journal of Biomedicine, 2024)
Hearing loss, recognized as one of the most prevalent sensory disorders, encompasses both syndromic and non-syndromic manifestations, with the identification of 87 genes and over 100 genetic loci in autosomal recessive non-syndromic hearing loss marking significant progress in understanding its genetic basis. In this case report, we showcase a non-syndromic hearing loss scenario involving a 21-year-old man experiencing progressive hearing loss. Through whole-exome sequencing, we unveiled a previously unreported homozygous mutation, c.1178_1179delAC; p.Tyr393Serfs*38, located in exon 2 (NM_016239.4) of the MYO15A gene in the proband. The newly identified mutation, causing a new reading frame (p.Tyr393Serfs*38), results in an early encounter with a stop codon, leading to the formation of a shortened protein. These findings advance our understanding of the molecular mechanisms involved in autosomal recessive non-syndromic hearing loss, contributing to broader scientific knowledge and potential breakthroughs in hearing loss research.